A calibrated, watershed-specific SCS-CN method: Application to Wangjiaqiao watershed in the three Gorges Area, China - Ling L.; Yusop Z.; Yap W.-S.; Tan W.L.; Chow M.F.; Ling J.L. (MDPI AG, 2023)
Abstracting; Curve fitting; Forecasting; Rain; Regression analysis; Runoff; Scandium; Soil conservation; Watersheds; Bootstrap; Curve numbers; Inferential statistics; Initial abstraction ratio; Linear regression models; Rainfall-runoff modeling; Residual sum of squares; Soil conservation service curve numbers; Infiltration; bootstrapping; calibration; confidence interval; error analysis; prediction; rainfall-runoff modeling; regression analysis; watershed; China